Inter-(c)are: Höpfl and Hanh's metaphorical mediation of intercorporeal ethicality. Issue 2 (15th March 2017) - Waistell, Jeff; Scherer, Bee
ABSTRACT: We identify one of Höpfl's key contributions; her metaphorical mediation of intercorporeal ethicality. Höpfl uses metaphor to communicate an ethics that is not based on cognitive, calculative and theorising rationality but is a state of being ethical that proceeds from the heart and a recognition of interconnected bodies. We direct the research question that emerges from Höpfl's work towards that of Thich Nhat Hanh, an Engaged Buddhist leader: how does his metaphorical discourse communicate the relationship between mindfulness and intercorporeal ethicality? Our analysis reveals how Hanh employs metaphors to mediate how mindfulness provides insight to our physical interdependence and thereby promotes mutual care: realising our indivisible unity, we care for each other. Key contributions are new theories of embodied ethicality (an ethics based on interconnected bodies) and embodying metaphor (metaphors that communicate the unity, interconnectedness and interdependence of bodies that care for one other).